2013
DOI: 10.4236/health.2013.510227
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome in type 2 diabetic patients: A comparative study using WHO, NCEP ATP III, IDF and Harmonized definitions

Abstract: To determine the prevalence of metabolic syndrome (MetS) in Malaysian type 2 diabetic patients using WHO, NCEP ATP III, IDF and the new Harmonized definitions, and the concordance between these definitions. This study involved 313 patients diagnosed with type 2 diabetes mellitus (T2DM) at two Malaysian tertiary hospitals. Socio-demographic data were assessed using a pre-tested interviewer-administered structured questionnaire. Anthropometric measurements were carried out according to standard protocols. Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 21 publications
5
25
4
1
Order By: Relevance
“…This result is similar to that obtained in a study performed in Bangladesh, where the percentage of individuals with altered blood sugar levels was 69% (16) .Regarding the similarity of high AC, the international literature emphasizes that patients with type 2 DM have similar or higher values than those from the study in question (16)(17) . Moreover, Malaysian researchers found that 92.9% of patients with type 2 DM had hypertriglyceridemia, higher than the results found in the present study (8) . The appearance of such imbalance is mainly due to the current inactive lifestyle of the population associated with inadequate eating habits, which generates innumerable cardio-metabolic complications, apart from MS.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…This result is similar to that obtained in a study performed in Bangladesh, where the percentage of individuals with altered blood sugar levels was 69% (16) .Regarding the similarity of high AC, the international literature emphasizes that patients with type 2 DM have similar or higher values than those from the study in question (16)(17) . Moreover, Malaysian researchers found that 92.9% of patients with type 2 DM had hypertriglyceridemia, higher than the results found in the present study (8) . The appearance of such imbalance is mainly due to the current inactive lifestyle of the population associated with inadequate eating habits, which generates innumerable cardio-metabolic complications, apart from MS.…”
Section: Discussioncontrasting
confidence: 90%
“…Regarding blood pressure and HDL cholesterol values, more than half of the sample managed to control such variables, although without relevance. However, the blood pressure levels found in study participants were better than those obtained in other studies, where high AP was observed in 90.4% of individuals (7)(8) . It should be noted that one of the main comorbidities associated with diabetes is precisely arterial hypertension, due to the sequence of changes linked to lack of metabolic control in this population.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…This definition was introduced very recently in 2009 to bring the harmony in the several existing definitions of the MetS [ 8 ]. Studies that have used this definition also reported very high prevalence of MetS confirming its improved performance in other diabetic population too [ 29 , 30 ]. Because of the very high cut-off points for waist circumference, NCEP definition could identify relatively low number of patients with central obesity.…”
Section: Discussionmentioning
confidence: 75%
“…In terms of the agreement between different MetS definition, one of the previous study conducted among Malaysian adult showed that the Harmonized definition exhibited good concordance with WHO and ATP III definitions (Tan et al 2013). However, another study also conducted among Malaysian adults reported better agreement between Harmonized and IDF definitions (Ramli et al 2013).…”
Section: Contrarilymentioning
confidence: 97%